2014
DOI: 10.1007/s10903-014-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Mood Among Within-Country Migrants in Periurban Shantytowns of Lima, Peru

Abstract: In low- and middle-income countries, migration to urban settings has reshaped the sprawl and socio demographic profiles of major cities. Depressive episodes make up a large portion of the burden of disease worldwide and are related to socio-demographic disruptions. As a result of terrorism, political upheaval, followed by economic development, Peru has undergone major demographic transitions over the previous three decades including large migrations within the country. We aimed to determine the prevalence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…Community-level characteristics have long been known to play a role in individual-level health outcomes in higher-income countries [11] and more recently in other countries throughout the world [12]. In Latin America, although ample work has shown that individual-level socio-demographics such as migrant status, employment, education, and income are associated with mental health [1316], very few studies have focused on the contextual, neighborhood-level determinants of mental disorders [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-level characteristics have long been known to play a role in individual-level health outcomes in higher-income countries [11] and more recently in other countries throughout the world [12]. In Latin America, although ample work has shown that individual-level socio-demographics such as migrant status, employment, education, and income are associated with mental health [1316], very few studies have focused on the contextual, neighborhood-level determinants of mental disorders [17].…”
Section: Introductionmentioning
confidence: 99%
“…Brazil in particular has recently experienced mass internal migration from lower-income rural areas to urban areas such as São Paulo, largely for education and employment opportunities [3]. Regions with recent terrorism or political upheaval such as Peru and Colombia have also seen heavy internal migration in recent years [16, 18]. The target cities of such migration often lack the infrastructure to house, employ, or provide general resources to larger populations [3, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Social variables associated with increased rates of depression include extreme poverty and overcrowding, amongst others [6, 7]. In addition, other common sociodemographic indicators associated with the presence of depression include variables such as: gender, age and marital status [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Cronbach’s alpha (α) was calculated to assess the reliability of CESD-R-20 Scale in this study, and values ranged from 0.830–0.927 for the 20 items in the current study sample. The Cronbach’s alpha coefficient for the 20-item-scale was 0.895, indicating a high internal consistency and that the removal of any of the items would have reduced the overall alpha marginally [ 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%